2020
DOI: 10.1101/2020.05.21.109678
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extracting the Dynamics of Behavior in Decision-Making Experiments

Abstract: Understanding how animals update their decision-making behavior over time is an important problem in neuroscience. Decision-making strategies evolve over the course of learning, and continue to vary even in well-trained animals. However, the standard suite of behavioral analysis tools is ill-equipped to capture the dynamics of these strategies. Here, we present a flexible method for characterizing time-varying behavior during decision-making experiments. We show that it successfully captures trial-to-trial cha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 43 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…One could imagine, for example, that a continuous state governing the animal’s degree of engagement drifts gradually over time, and that the GLM-HMM simply divides these continuous changes into discrete clusters. To address this possibility, we fit the data with PsyTrack, a psychophysical model with continuous latent states [55, 56]. The PsyTrack model describes sensory decision-making using an identical Bernoulli GLM, but with dynamic weights that drift according to a Gaussian random walk (see Methods sec.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One could imagine, for example, that a continuous state governing the animal’s degree of engagement drifts gradually over time, and that the GLM-HMM simply divides these continuous changes into discrete clusters. To address this possibility, we fit the data with PsyTrack, a psychophysical model with continuous latent states [55, 56]. The PsyTrack model describes sensory decision-making using an identical Bernoulli GLM, but with dynamic weights that drift according to a Gaussian random walk (see Methods sec.…”
Section: Resultsmentioning
confidence: 99%
“… (a) Cross-validation performance of the 3 state GLM-HMM compared to PsyTrack [55, 56] for all 37 mice studied (each individual line is a separate mouse; black is the mean across animals). Test loglikelihood is considerably higher for all mice for the GLM-HMM than for PsyTrack, which assumes that the mouse uses a set of smoothly evolving GLM weights to make its decision at each trial.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results show that V1 activity is systematically modulated by the task the animal is engaged in. Recent behavioral explorations have demonstrated that the rule that the animal bases its decisions on can change during a behavioral session, even when the task structure remains unchanged (Roy et al, 2020). It will be important to see whether such spontaneous changes in behavioral strategy are reflected in V1 activity in a similar manner to how changes in task context are represented.…”
Section: Discussionmentioning
confidence: 99%